Resistance pattern of white oat genotypes to crown rust in the definition of crosses - Vieira, Eduardo Alano; Carvalho, Fernando Irajá Félix de; Chaves, Márcia Soares; Oliveira, Antonio Costa de; Bertan, Ivandro; Martins, Andreza Figueirola; Hartwig, Irineu; Benin, Giovani; Valério, Igor Pirez; Fonseca, Daniel Andrei Robe (Pesquisa Agropecuaria Brasileira, 2006)
The objectives of this work were: to determine the resistance/susceptibility pattern of 20 elite oat genotypes to 40 isolates of Puccinia coronata f. sp. avenae; to determine the pattern of virulence/avirulence of isolates collected in three counties of Rio Grande do Sul to the oat genotypes studied; and to indicate potential parents for the generation of populations with high crown rust resistance. The resistance pattern of oat genotypes and the virulence/avirulence of the fungi were determined by the analysis of the reaction incited by the inoculation of Puccinia coronata f. sp. avenae isolates into seedlings of oat genotypes. The selection of genitors was based on the cultivar complementation index proposed in this work. Genotypes expressing resistance to the larger number of isolates were FAPA6, URS20, UPFA20, CFT1 and FAPA5, while UFRGS15, UPF15, UPF18, UPF19 and UPF16 were susceptible to a higher number of isolates. The following crosses are indicated: FAPA6 x Albasul, URS22 x FAPA6, CFT1 x URPEL15 and CFT1 x UFRGS19.